GEOLOGY AND 3-D STATIC RESERVOIR MODELLING OF FS2âFS7 PARASEQUENCE INTERVAL, PUCANGAN FORMATION, WASID FIELD, NORTH EAST JAVA BASIN - Wisnu Setyawardana, Farid
Wasid Field is one of the gas produced field located in Brantas Block, North East Java Basin, East Java Province. Wasid Field has an area of approximately 56 km2 which had already been produced since 1998. This study was conducted at FS2-FS7 parasequence interval in Pucangan Formation. This study was purposed to determine facies association, depositional environment, facies distribution, sequence stratigraphy correlation, petrophysics property, build static three-dimensional facies and petrophysics model as well as estimate the hydrocarbon volume in place. Data used in this study are core description report, final well report, biostratigraphy report, drill stem test, well log data of 19 wells, and 2-D seismic line. The result of lithofacies analysis showed that the lithofacies comprising FS2-FS7 parasequence interval were six sandstone lithofacies namely Sm, Sr, Scl, Ss, Spm, and Spb and four mudstone lithofacies namely Md, Mr, Ms, and Msr. These lithofacies were grouped into three facies associations in the form of distributary channel, crevasse splay, and floodplain. Based on the facies association analysis, biostratigraphic reports, and electrofacies, the study interval was upper delta plain with southwest-northeast depositional direction. Sequence stratigraphy analysis showed that reservoirs are lowstand system tract deposit with depletion of reservoir interval deposit to the northeast. Petrophysical analysis shows the distributary channel and crevasse splay facies can be the potential reservoir. The seismic interpretation results at the research interval show the presence of a thrust fault with west-east direction and an anticline with west-east trend. Facies reservoirs distribution were built based on distributary channel model and crevasse splay which is controlled by depositional direction. The distribution of petrophysical properties reservoirs were carried out on the facies model. The estimation result of the total remaining gas volume in place as of March 2006 from the total reservoir zone is 10.33 BSCF.